Characterization and Comparative Genomics Analysis of lncFII Multi-Resistance Plasmids Carrying blaCTX–M and Type1 Integrons From Escherichia coli - Zhou, Wei; Zhang, Enbao; Zhou, Jinzhi; He, Ze; Zhou, Yuqiao; Han, Jianzhong; Qu, Daofeng (Frontiers in Microbiology, 2021)
Abstract This research aimed to investigate the presence and transferability of the extended-spectrum β-lactamase resistance genes to identify the genetic context of multi-drug resistant (MDR) loci in two Escherichia coli plasmids from livestock and poultry breeding environment. MICs were determined by broth microdilution. A total of 137 E. coli resistant to extended-spectrum β-lactam antibiotics were screened for the presence of the ESBL genes by PCR. Only two E. coli out of 206 strains produced carbapenemases, including strain 11011 that produced enzyme A, and strain 417957 that produced enzyme B. The genes were blaKPC and blaNDM, respectively. The plasmids containing blaCTX-M were conjugatable, and the plasmids containing carbapenem resistance gene were not conjugatable. Six extended-spectrum β-lactamase resistance genes were detected in this research, including blaTEM, blaCTX-M, blaSHV, blaOAX-1, blaKPC and blaNDM, and the detection rates were 94.89% (130/137), 92.7% (127/137), 24.81% (34/137), 20.43% (28/137), 0.72% (1/137), and 0.72% (1/137), respectively. Two conjugative lncFII multi-resistance plasmids carrying blaCTX-M, p11011-fosA and p417957-CTXM, were sequenced and analyzed. Both conjugative plasmids were larger than 100 kb and contained three accessory modules, including MDR region. The MDR region of the two plasmids contained many antibiotic resistance genes, including blaCTX-M, mph (A), dfrA17, aadA5, sul1, etc. After transfer, both the transconjugants displayed elevated MICs of the respective antimicrobial agents. A large number of resistance genes clusters in specific regions may contribute to the MDR profile of the strains. The presence of mobile genetic elements at the boundaries can possibly facilitate transfer among Enterobacteriaceae through inter-replicon gene transfer. Our study provides beta-lactam resistance profile of bacteria, reveals the prevalence of β-lactamase resistance genes in livestock and poultry breeding environment in Zhejiang Province, and enriches the research on IncFII plasmids containing blaCTX-M.